The Influence of Technology and Parent Participation on Early Childhood Learning at Sirajul Ulum Kindergarten - Nur Indah Kumala Sari; Siti Maryam; Debby Adelita (Journal of Childhood Development, 2024)
In this digital era, the use of technology has become a significant topic in early childhood education, significantly impacting the learning process. This study analyzes the influence of technology and parental participation on early childhood education at RA Sirajul Ulum. Through a quantitative approach, this research explores the relationship between the use of technology, such as interactive learning applications, and the role of parents in guiding early childhood learning. The study population includes all early childhood students enrolled at RA Sirajul Ulum, with a sample taken from two groups: the intensive technology use group and the less intensive technology use group. The results of the study show that intensive use of technology among early childhood students is positively associated with increased motivation and participation in the learning process. Additionally, parental involvement in guiding technology use has enhanced children's understanding of the learning material. These findings provide deeper insights into how technology and parental participation can influence early childhood education at this institution, highlighting the importance of collaboration between technology and parental involvement to achieve optimal learning outcomes.